2002
DOI: 10.1007/s00330-002-1354-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study in patients with microcalcifications: full-field digital mammography vs screen-film mammography

Abstract: The goal of this prospective study was to compare a fullfield digital mammography system (FFDM) to a conventional screenfilm mammography system (SFM) for the detection and characterization of microcalcifications. Fifty-five patients with 57 isolated microcalcification clusters were examined using a FFDM system (Senographe 2000D, GE Medical Systems, Milwaukee, Wis.) and a SFM system (Senographe DMR, GE Medical Systems, Milwaukee, Wis.). A conventional screen-film mammogram and a digital contact mammogram were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(45 citation statements)
references
References 13 publications
4
36
0
5
Order By: Relevance
“…Currently, greater than 90% mammography units operating in the United States are digital rather than film, 33 and studies have shown improved performance of digital mammography compared to film screen mammography in women with dense breast tissue. 6, 34, 35 While studies of film mammography have demonstrated declining sensitivity with increasing breast density, 6, 36 a more recent study of 231,034 digital mammograms from four mammography registries in the Breast Cancer Surveillance Consortium showed significantly improved sensitivity of digital mammography compared to film screen mammography in women with dense breast tissue. 6 Although not perfect, mammography is still the only screening test whose ability to reduce breast cancer mortality has been proven.…”
Section: Commentmentioning
confidence: 99%
“…Currently, greater than 90% mammography units operating in the United States are digital rather than film, 33 and studies have shown improved performance of digital mammography compared to film screen mammography in women with dense breast tissue. 6, 34, 35 While studies of film mammography have demonstrated declining sensitivity with increasing breast density, 6, 36 a more recent study of 231,034 digital mammograms from four mammography registries in the Breast Cancer Surveillance Consortium showed significantly improved sensitivity of digital mammography compared to film screen mammography in women with dense breast tissue. 6 Although not perfect, mammography is still the only screening test whose ability to reduce breast cancer mortality has been proven.…”
Section: Commentmentioning
confidence: 99%
“…The spatial resolution of DM, however, is limited by pixel size. Despite this limitation, it has been found that the detection of microcalcifications on DM is equal to, if not better than, that of SFM [10, 11] (Figure 1). In a study by Fischer U et al, DM showed more calcification compared to SFM, having a higher sensitivity and reliability in characterising microcalcification.…”
Section: Performance Of Digital Mammography (Dm)mentioning
confidence: 99%
“…In a study by Fischer U et al, DM showed more calcification compared to SFM, having a higher sensitivity and reliability in characterising microcalcification. This is due to the increased contrast resolution of DM which enhances its ability to visualise small high-contrast structures such as microcalcification [10]. …”
Section: Performance Of Digital Mammography (Dm)mentioning
confidence: 99%
“…Mammography is divided into discrete processes: image acquisition, image display, and image storage, so each can be optimized separately [13]. FFDM allows real-time image presentation, postimage processing, and digital storage [14, 15]. Digital mammographic images can be transmitted electronically (e.g., via the Internet) in a process known as telemammography [13], allowing the radiologist and the clinician to review the images from a remote location.…”
Section: Commonly Used Methodsmentioning
confidence: 99%